The Anomalous of the Uniformity - Valencia López, Daniel Felipe (Disertaciones, 2019)
The Anomalous of the Uniformity states the way how power constitues knowledge and social practices give place to a series of habitual life forms que, if violated or trasngreses, give way to diferents forms of monstruosity. More than an Entity, the monster is a conceptual operation, evidencing categories, canons and habitual forms of life demanded, internalized and spread by a society among the individuals through their world views. Since the XVIII century those facts gave place to a great preocupation for the anormal expressed in diferent studies of biology, psychiatry, medicine and politics. This papper suggest how the conceptions developed by Michel Foucault about power, domination and criminality explain how were built our conceptios of monstrousity and anormality. In a further development, this investigation will be related to some of the main gothic novels.